A centralidade da angústia na obra de Georges Bataille - Ferreira, Silvia Raimundi (2024)
This doctoral thesis argues the hypothesis that angst is the central element in the work of Georges Bataille that arises in his fictional narratives and in his philosophical and social studies. The argument for this theory follows a reading of the works Story of the Eye, Madame Edwarda, and My Mother, as well as more theoretical writings in which the author achieves his declared desire of destabilizing the reader. The concept of angst is approached through the writings of Sigmund Freud and Jacques Lacan, psychoanalysts who theorized about this affect and who, with their contribution, allow a more in-depth access to the work of the given writer. The knot of angst, the convergence of the heterogeneous Real, Symbolic and Imaginary, are the link that binds and authorizes this research.